Distribusi Kelimpahan Mikroplastik Pada Sedimen Sungai Sibam, Pekanbaru, Riau - Muhammad Hasbu Nazar; Lita Darmayanti; Gunadi Priyambada (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Microplastics are one of the major threats to ecosystems in rivers. Microplastic is the smallest part of plastic measuring <5 mm which if it enters the environment it will accumulate in the waters and is not easily removed because of its persistent nature. The abundance of microplastics is strongly influenced by their activities and pollutant sources. The Sibam River is a tributary that empties into the Siak River. The high activity along the river and the presence of settlements are thought to be the distribution route for microplastics to the river. The purpose of this study was to determine the abundance and types of microplastics in the Sibam River, Pekanbaru Riau. The abundance of microplastics obtained was based on 3 segments, which ranged from 4.444-11,555 particles/kg dry sediment. The types of microplastics found in this study were fiber (15.38%), film (40.38%), and fragments (44.24%).Keywords: microplasty, abundance, sediment, Sibam River